The complete mitochondrial genome of Tropidothorax sinensis (Reuter, 1888) (Hemiptera: Lygaeidae) - Weidong Huang; Siyu Gong; Yunfei Wu; Fan Song; Hu Li (Mitochondrial DNA. Part B. Resources, 2021)
The complete mitochondrial genome (mitogenome) of Tropidothorax sinensis (Reuter, 1888) was determined in the present study by using high-throughput sequencing. This mitogenome is 15,422 bp in size and comprises 37 typical coding genes and a control region. All protein-coding genes are initiated with ATN, except for COX1 and ND4L use TTG as the start codon, and terminate with TAA or TAG with the exception of COX2, COX3 and ND1 which use a single T residue as the stop codon. Twenty-one of the 22 transfer RNA genes have the typical clover-leaf structure except for tRNASer(AGN). The monophyly of the family Lygaeidae and the sister relationship between T. sinensis and T. cruciger is supported by maximum likelihood analysis based on the protein-coding and ribosomal RNA gene sequences.